A Choreographer's Approach to Opera. (November 2015) - Collins, Aletta
Abstract : My first professional commission as a choreographer was not for a dance company but for an opera company, for the Bregenz Festival in Austria. In 1988, while I was still a student at London Contemporary Dance School, I was approached to choreograph Camille Saint-Saëns's Samson et Dalila; the commission also included giving 'movement' to the chorus (a group of 120 singers) and directing the dancers when they were not dancing. The dancers were a classical company from Sofia, Bulgaria, a company of thirty none of whom spoke English.